Murine Intrarectal Instillation of Purified Recombinant Clostridioides difficile Toxins Enables Mechanistic Studies of Pathogenesis - Markham, Nicholas O. (Infect Immun, 2021)
Clostridioides difficile is linked to nearly 225,000 antibiotic-associated diarrheal infections and almost 13,000 deaths per year in the United States. Pathogenic strains of C. difficile produce toxin A (TcdA) and toxin B (TcdB), which can directly kill cells and induce an inflammatory response in the colonic mucosa. Hirota et al. (S. A. Hirota et al., Infect Immun 80:4474–4484, 2012) first introduced the intrarectal instillation model of intoxication using TcdA and TcdB purified from VPI 10463 (VPI 10463 reference strain [ATCC 43255]) and 630 C. difficile strains. Here, we expand this technique by instilling purified, recombinant TcdA and TcdB, which allows for the interrogation of how specifically mutated toxins affect tissue. Mouse colons were processed and stained with hematoxylin and eosin for blinded evaluation and scoring by a board-certified gastrointestinal pathologist. The amount of TcdA or TcdB needed to produce damage was lower than previously reported in vivo and ex vivo. Furthermore, TcdB mutants lacking either endosomal pore formation or glucosyltransferase activity resemble sham negative controls. Immunofluorescent staining revealed how TcdB initially damages colonic tissue by altering the epithelial architecture closest to the lumen. Tissue sections were also immunostained for markers of acute inflammatory infiltration. These staining patterns were compared to slides from a human C. difficile infection (CDI). The intrarectal instillation mouse model with purified recombinant TcdA and/or TcdB provides the flexibility needed to better understand structure/function relationships across different stages of CDI pathogenesis.